Penerapan Joging untuk Menurunkan Kadar Gula Darah Puasa pada Penderita Diabetes Mellitus Tipe 2 di Keluarga Wilayah Puskesmas Sekaran Semarang - Diana Dayaningsih; Shella Difanda Putri (PPNI UNIMMAN, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by increased blood glucose (hyperglycemia). The aim of the case study is to describe the application of jogging to reduce fasting blood sugar levels in people with type 2 diabetes mellitus. The research used descriptive research with jogging carried out 3 times during 3 consecutive days for 30 minutes by checking fasting blood sugar before and after jogging. Researchers used 2 clients whose inclusion did not have dangerous diseases such as heart disease, kidney failure, asthma. Have a history of Type 2 Diabetes Mellitus for more than 2 years, age more than 45 years, no diabetes mellitus wounds on the legs, fasting blood sugar measurement results before the procedure 126mg/dl – 200mg/dl. Subject 1's results from measuring pre-test fasting blood sugar levels were 175 mg/dl and post-test results were 166 mg/dl. The results of subject 2 from measuring pre-test fasting blood sugar levels were 134 mg/dl, and the post-test results were 127 mg/dl, the results of both subjects experienced a significant decrease in fasting blood sugar levels. The results of this case study are the basis for further case studies, especially those related to jogging or other physical activities for people with type 2 diabetes mellitus.